Wpływ zmysłu wzroku na poczucie równowagi ogólnej = The influence of the sense of sight for a sense of general balance - T. Kowalik; A. Srokowska; A. Lewandowski; Z. Piekorz; W. Zukow (Kazimierz Wielki University, 2015)
Kowalik T., Srokowska A., Lewandowski A., Piekorz Z., Zukow W. Wpływ zmysłu wzroku na poczucie równowagi ogólnej = The influence of the sense of sight for a sense of general balance. Journal of Education, Health and Sport. 2015;5(11):720-726. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.44343 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A720-726 http://pbn.nauka.gov.pl/works/688201 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015.   Wpływ zmysłu wzroku na poczucie równowagi ogólnej The influence of the sense of sight for a sense of general balance   Kowalik T.1, Srokowska A.1, Lewandowski A.1, Piekorz Z.2, Zukow W3   • Katedra i Zakład Podstaw Kultury Fizycznej, Collegium Medicum w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu • Katedra Fizjoterapii, Collegium Medicum w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu • Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy     Abstrakt             Celem pracy jest zbadanie wpływu zmysłu wzroku na poczucie równowagi ogólnej. Badanie przeprowadzono za pomocą próby równowagi ogólnej testem Eurofit.             Zbadano 81 kobiet oraz 30 mężczyzn - studentów kierunku fizjoterapii.             Badania wykazały bardzo duże różnice między testem o oczach otwartych a testem o oczach zamkniętych, co w pełni potwierdza zależność zmysłu równowagi od zmysłu wzroku.   Abstract             The aim of the study is to examine the impact of the sense of sight for a sense of general balance.                 The survey was conducted using the Eurofit test. It was examined 81 women and 30 men - students of physiotherapy.                 Studies have shown very large differences between the test with eyes open and eyes closed on the test, which fully confirms the dependence of sense of balance of the sense of sight.   Słowa kluczowe: niewidomi, zmysł równowagi, studenci, Eurofit.   Key words: blind, sense of balance, students, Eurofit.